2009
DOI: 10.1002/jsfa.3683
|View full text |Cite
|
Sign up to set email alerts
|

Determination of purine alkaloids and catechins in different parts of Camellia assamica var. kucha by HPLC‐DAD/ESI‐MS/MS

Abstract: BACKGROUND: Kucha (Camellia assamica var. kucha) is a novel wild tea resource grown in China and a tea plant containing a sizable amount of theacrine (1,3,7,9-tetramethyluric acid). High-performance liquid chromatography (HPLC) analysis of purine alkaloids and catechins in young leaves of Kucha has been reported previously. However, the compositions of purine alkaloids and catechins in other parts of the plant remain unknown, and more information about the chemical constituents of Kucha is also necessary for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The difference between molecular mass and aglycone mass suggested that peaks 37 and 42 were a hexoside and a pentoside, respectively. Based on these information and comparison with the literature data, peaks 37 and 42 were tentatively identified as a myricetin hexoside and a myricetin pentoside, respectively (de Brito, de Araujo, Lin, & Harnly, 2007;Lu et al, 2009). Similarly, peaks 46 and 48 were tentatively identified as a kaempherol hexoside and a quercetin-O-pentoside, respectively.…”
Section: Flavonoidsmentioning
confidence: 98%
“…The difference between molecular mass and aglycone mass suggested that peaks 37 and 42 were a hexoside and a pentoside, respectively. Based on these information and comparison with the literature data, peaks 37 and 42 were tentatively identified as a myricetin hexoside and a myricetin pentoside, respectively (de Brito, de Araujo, Lin, & Harnly, 2007;Lu et al, 2009). Similarly, peaks 46 and 48 were tentatively identified as a kaempherol hexoside and a quercetin-O-pentoside, respectively.…”
Section: Flavonoidsmentioning
confidence: 98%
“…These structures are based on xanthine or uric acid skeletons ( Fig. kucha; Lu et al, 2009;Zheng, Ye, Kato, Crozier, & Ashihara, 2002). Methyl groups originating from S-adenosyl-L-methionine (SAM) are attached to nitrogen atoms at positions 1, 3, 7, 9 or an oxygen atom at position 2.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent MS 3 analysis of the ion at m / z 191 produced fragments also observed for quinate standard, while the ion at m / z 169 yielded a fragment with m / z 125, consistent with gallate, and compound 2 was therefore identified as galloyl quinate. The fragmentation pattern of peak 10 with m / z 441 was similar to that reported for epicatechin‐3‐gallate (Del Rio et al ., ; Lu et al ., ), and MS 3 analysis of the main MS 2 fragments with m / z 289 and m / z 169 yielded ions characteristic for epi/catechin ( m / z 245, 205 and 179) and gallate ( m / z 169), respectively, supporting the identification of this compound as epi/catechin gallate. Similarly, compounds 9 (M r 472 Da) and 11 (M r 456 Da) showed fragmentation patterns consistent with flavan‐3‐ol methyl gallates and were identified as epi/gallocatechin methyl gallate and epi/catechin methyl gallate, respectively, which are less common constituents of tea leaves (Sano et al ., ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 99%